Environmental Accounting for Oil and Natural Gas : a North American Case Study of Canada and the Southeast United States. - Merem, Edmund C. (Edwin Mellen Press, 2010)
This book uses national accounting approach anchored in multivariate analysis and descriptive statistics connected to Geographic Information Systems (GIS) technology to analyse oil and gas depletion and environmental damage costs and the factors responsible for the change from 1961 to 2000. This book contains two color photographs.